Effect of orthodontic treatment on alveolar bone thickness in adults: a systematic review - Michelle Sendyk; Daniele Sigal Linhares; Claudio Mendes Pannuti; João Batista de Paiva; José Rino Neto
ABSTRACT Objectives: This review aimed at evaluating changes in alveolar bone thickness after completion of orthodontic treatment. Methods: Only prospective clinical studies that reported bone thickness in adult patients undergoing non-surgical orthodontic treatment were considered eligible. MEDLINE, EMBASE and LILACS databases were searched for articles published up to July 2018. Results: A total of 12 studies met the selected criteria. Most of the studies showed that orthodontic treatment produces a reduction in bone thickness of incisors, mainly at the palatal side. Conclusion: On patients undergoing different orthodontic treatment techniques, there was a significant bone thickness reduction, mainly on the palatal side. Clinical relevance: These findings are relevant and have to be considered in diagnosis and planning of tooth movement, in order to prevent the occurrence of dehiscence and fenestration in alveolar bone.